The Influence of Emotional Maturity on Aggressive Behavior in Junior High School Students with School Climate as a Moderator Variable - Wihadi, Sudira; Sulistyani, Nuraida Wahyu; Umaroh, Siti Khumaidatul (KnE Social Sciences, 2024)
Aggressive behavior is a common problem among both the general public and students. It is disliked in society because it creates a sense of insecurity and has harmful consequences, ranging from physical injury to psychological damage. This study examines the influence of emotional maturity on aggressive behavior with school climate as a moderating variable. A total of 87 students from Bhakti Loa Janan Junior High School, consisting of grades 7, 8, and 9, participated in this study. The study used three valid and reliable measuring instruments, consisting of an aggression scale, school climate, and emotional maturity. The results of the study showed that school climate was not proven to be a moderating variable between emotional maturity and student aggression with a significant value (p) of 0.168. Keywords: emotional maturity, aggressive behavior, school climate